Para un conocimiento alternativo de las alternativas. A propósito de Boaventura de Sousa Santos - José Guadalupe Gandarilla Salgado (Revista Crítica de Ciências Sociais, 2008)
Engaging with the work of Boaventura de Sousa Santos, this article goes on to discuss the pertinence and the possibilities for development of forms of thought posing an alternative to the modes of social and political knowledge of the world which held a position of dominance and hegemony within Western modernity.